Teaching-learning of psychology: reflections from interbehavioral scientific matrix - Reyna, Winter (2017)
In previous works it has been pointed out that the exercise of Psychology is not limited to a single type of practice; On the contrary, psychologists perform philosophical, theoretical, technological, professional and transdisciplinary practices. Derived from the above in the present work, it is argued that teaching-learning Psychology demands that the aforementioned practices be taught-learn, to a greater or lesser extent. Based on this, (a) the specific characteristics of each practice are described roughly; (b) there is an aroused presentation of the main interbehavioral theoretical contributions regarding the teaching-learning of Psychology, the didactic interaction and the teacher's performance, which have focused on the learning of the practice of scientific investigation and its teaching; and, derived from the previous points, (c) some reflections are presented regarding the teaching practice of psychology, as well as the learning of it, taking into account the different practices that are carried out in this discipline and not only with respect to the research practice. In the final comments, the benefits of the distinction of psychological practices in the training of apprentices of the discipline are indicated.